Contesting Religion and Ethnicity in Madurese Society - Akhmad Siddiq; Leonard C Epafras; Fatimah Husein (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2018)
Abstract: This paper describes historical phases of Madurese identity construction, the origins of Madurese ethnicity, inter-ethnic and inter-cultural relation, Madurese Pendalungan culture, and how Islam involves into cultural identities of the Madurese. In this paper, I will argue that Islam has become part of cultural values of the Madurese, that is, embedded within traditional activities and local wisdom. However, the involvement does not mean to exclude other “non-Islamic” and “non-Madurese” tradition in the process of construing Madurese identity. By exploring how Madurese identity was culturally constructed we could be able to draw more visible connection between religion, tradition, and social identity. This paper illustrates how Madurese identity culturally produced, nurtured, and matured. Since identity is a way of perceiving, interpreting, and representing the existence of people, I persist that Madurese identity has also been produced and reproduced depending on political, social, and cultural situation. In this regard, inter-religious or inter-ethnic relation remains important. [Artikel ini menjelaskan fase terbentuknya identitas orang-orang Madura, asal-usul etnis, hubungan lintas-budaya dan antaretnis, budaya Pendalungan, dan bagaimana Islam berinteraksi dengan identitas budaya orang Madura. Dalam artikel ini saya meneguhkan bahwa Islam telah menjadi bagian tak terpisahkan dari nilai-nilai budaya Madura, yang bisa dilihat dari dalam aktivitas sosial dan kearifan lokal orang Madura. Meski demikian, hal ini tidak menafikan bahwa tradisi “non-Islam” atau “non-Madura” juga memiliki peran dalam proses pembentukan identitas Madura. Dengan mengurai proses konstruksi identitas sosial Madura, seseorang bisa melihat dengan lebih jelas hubungan erat antara agama, tradisi, dan identitas sosial. Artikel ini juga menggambarkan bagaimana identitas Madura diproduksi, dikembangkan, dan dilestarikan. Sebab identitas adalah sebuah persepsi, interpretasi, dan representasi, artikel ini menyimpulkan bahwa identitas Madura pun tidak lepas dari tahapan itu: bergantung pada kondisi politik, sosial, ekonomi dan budaya. Dalam konteks ini, relasi antaragama dan antaretnis menjadi sangat penting.]